Alteración de glucemia basal y de tolerancia a la glucosa en rattus norvegicus variante albinus expuestas al humo lateral del cigarrillo - Choquehuanca Baltodano, Nadia Paola (2014)
To establish whether exposure to sidestream smoke produces glucose and impaired glucose tolerance in Rattus norvegicus albinus variety. Materials and Methods: 16 male Holtzman rats, of which 8 were in the control group and the experimental 8 were used. Glucose sample was taken both groups on day 0 of the exposure, then the experimental group was challenged with the sidestream smoke 100-300ppm at a concentration of carbon monoxide. At the 4th week test oral glucose tolerance test was performed in both groups, after 12 hours of nocturnal fasting, fasting glucose determined after glucose at 30, 60 and 120 minutes after administration of glucose. At the end of 8 weeks the test oral glucose tolerance test was repeated. Results: A significant difference (p <0.05) were observed by fasting glycemia exposed to 4 weeks of exposure (104 vs 139.5 mg/dl), the same happened in baseline blood glucose before exposure with glycemia at 8 weeks of exposure (p <0.05). Also when comparing the experimental and control groups there were significant difference (p <0.05) between the curves of glucose tolerance at 8 weeks of exposure. Conclusions: Exposure to sidestream smoke produces alteration in the curve of glucose tolerance and increased fasting glucose, to produce diabetes mellitus in the future